2017
DOI: 10.5423/ppj.oa.10.2016.0205
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Tissue Culture in Virus Elimination from Caprifig and Female Fig Varieties (Ficus carica L.)

Abstract: Fig mosaic disease (FMD) is a viral disease that spreads in all Tunisian fig (Ficus carica L.) orchards. RT-PCR technique was applied to leaf samples of 29 fig accessions of 15 fig varieties from the fig germplasm collection of High Agronomic Institute (I.S.A) of Chatt-Mariem, to detect viruses associated to FMD. Analysis results show that 65.5% of the accessions (19/29) and 80.0% (12/15) of the fig varieties are infected by FMD-associated viruses. From all fig accessions, 41.4% of them are with single infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…In comparison with our findings, all 137 tested trees from all cultivars were infected by at least one virus, with FMV and FLMaV-2 being the most prevalent viruses with incidence rates of 49% and 21.8% in all tested plants, respectively, followed by FLMaV-1 with an incidence rate of 10.9% in all tested plants. Our findings corroborate prior reports from a number of Mediterranean countries [ 1 , 2 , 7 , 23 , 34 , 37 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In comparison with our findings, all 137 tested trees from all cultivars were infected by at least one virus, with FMV and FLMaV-2 being the most prevalent viruses with incidence rates of 49% and 21.8% in all tested plants, respectively, followed by FLMaV-1 with an incidence rate of 10.9% in all tested plants. Our findings corroborate prior reports from a number of Mediterranean countries [ 1 , 2 , 7 , 23 , 34 , 37 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…The common fig ( Ficus carica L., Moraceae ) was one of the first cultivated fruit crops in the Mediterranean region, which is now regarded as the world's leading fig-producing region [ 1 , 2 ], and it is very important in Egypt [ 3 ]. Fig fruits may be eaten fresh or dried and are known for their moderate laxative properties [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of electrophoresis agarose gel was used in 1.7% concentration with addition of normal strength Tris Borate buffer coloured by ethydium bromide in 0.5 µg/ml concentration at the voltage of 100 V for 45 minutes with the further photographic documentation of amplicons in ultraviolet light and processing in AdobePhotoshop 7.0 program. The obtained results were analyzed through the use of CrossChecker 2.91 software with transfer of data into binary matrices on the grounds of presence or absence of polymorphous fragments uniform in size [15].…”
Section: Methodsmentioning
confidence: 99%
“…Explant size is an important aspect to both regenerate the apical meristems and achieve sanitation. Bayoudh et al (2017) found that the best tissue size to eradicate Feline calicivirus (FCV) and Fig mild mottle associated virus (FMMaV) (70% to 90% success rates) in the Ficus carica L. species measured approximately 0.5 mm; this agrees with research conducted in cassava in which Deepthi and Makeshkumar (2016) eliminated 100% SCMV and Indian cassava mosaic virus (ICMV) when the 53 apical meristems were between 0.1 and 0.5 mm, sizes very similar to those of the MSXJ hybrid (0.3 mm). In addition, studies conducted by Al-Taleb et al (2011) and Hossain and Levy (2014) in potato showed the benefits of eliminating Potato virus Y (PVY) and Potato virus X (PVX) (75% to 100%), which are similar to PRSV because they are potyviruses and cause substantial economic losses in the crops they infect.…”
Section: In Vitro Culture Of Meristemsmentioning
confidence: 99%